Low angiomotin‐p130 with concomitant high Yes‐associated protein 1 expression is associated with adverse prognosis of advanced gastric cancer. Issue 11 (8th September 2017) - Hong, Soon Auck; Son, Myoung Won; Cho, Junhun; Jang, Si‐hyong; Lee, Hyun Ju; Lee, Ji‐Hye; Cho, Hyun Deuk; Oh, Mee‐Hye; Lee, Moon Soo
Abstract : Angiomotin (AMOT) promotes angiogenesis and plays a role in neovascularization during tumorigenesis. Recently, the AMOT isoform, AMOT‐p130, was shown to exert a regulatory effect on Yes‐associated protein 1 (YAP1), a major downstream effector of the Hippo pathway. The specific roles of AMOT‐p130 and YAP1 in advanced gastric cancer (AGC) are yet to be established. In this study, a total of 166 patients with AGC were enrolled, and AMOT‐p130 and YAP1 levels were analyzed by immunohistochemistry using tissue microarrays. Low AMOT‐p130 together with high YAP1 expression (n = 30, 18.1%) was associated with high T stage (p = 0.042), high TNM stage (p = 0.025), and venous invasion (p = 0.048). A Kaplan–Meier survival analysis with log‐rank test revealed a significant correlation with decreased AMOT‐p130 coupled with high nuclear YAP1 expression with shorter overall survival (p = 0.0045) and disease‐free survival (p = 0.0028). Furthermore, multivariate analyses showed that the low AMOT‐p130/high YAP1 expression profile was an independent prognostic factor for disease‐free survival (p = 0.008, HR = 1.874, CI, 1.177–2.986) and overall survival (p = 0.012, HR = 1.903, CI, 1.152–3.143). Our findings collectively demonstrate that low AMOT‐p130 combined with high YAP1 expression is correlated with an unfavorable AGC prognosis.